2013
DOI: 10.5966/sctm.2013-0135
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Human Leukocyte Antigen-A*0201-Restricted, Cytotoxic T Lymphocyte Epitopes on CD133 for Cancer Stem Cell Immunotherapy

Abstract: Targeting cancer stem cells (CSCs) with immunotherapy may be an effective means to prevent recurrences in glioblastoma multiforme (GBM). It is well established that CD133 is expressed in the population of GBM tumor cells representing CSCs. This raises a possibility that CD133 could serve as a potential target for cytotoxic T cells (CTLs) to target glioblastoma cancer stem cells. Two potential human leukocyte antigen (HLA)-A*0201-restricted CD133 epitopes, ILSAFSVYV (CD133-405) and YLQWIEFSI (CD133-753), showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 27 publications
1
11
1
Order By: Relevance
“…Immunization of mice with the murine homologs of the CD133 epitopes demonstrated immunogenicity in the absence of autoimmune damage. The study supports the use of CD133‐specific epitope vaccines to target CSCs in glioblastoma, and argues for a clinical trial to assess the safety of this approach .…”
Section: Glioma and Glioblastomasupporting
confidence: 59%
“…Immunization of mice with the murine homologs of the CD133 epitopes demonstrated immunogenicity in the absence of autoimmune damage. The study supports the use of CD133‐specific epitope vaccines to target CSCs in glioblastoma, and argues for a clinical trial to assess the safety of this approach .…”
Section: Glioma and Glioblastomasupporting
confidence: 59%
“…Recently, the potentials of immunotherapy targeting CSC antigens has been demonstrated by Ji et al who reported the usefulness of CD133‐derived epitopes in the context of HLA‐A2 to induce CTLs to reject glioblastoma. The number of CSCs/CICs is very low compared with the other populations, so they might be efficiently rejected by the limited number of peptide‐specific CTLs in vivo . Dillman et al also suggested the potentials of CSC antigen‐based vaccines for melanoma …”
Section: Future Perspectives: Peptide Vaccination Therapy Targeting Cmentioning
confidence: 99%
“…The number of CSCs/CICs is very low compared with the other populations, so they might be efficiently rejected by the limited number of peptide-specific CTLs in vivo. 62 Dillman et al also suggested the potentials of CSC antigen-based vaccines for melanoma. 63 On the other hand, it is hard to eradicate a large tumor burden by peptide vaccination alone.…”
Section: Future Perspectives: Peptide Vaccination Therapy Targeting Cmentioning
confidence: 99%
“…This particular subpopulation of cells is therefore the ideal candidate for vaccine therapy. Ji et al took advantage of CD133, a proposed marker of gCSCs, as a target to stimulate cytotoxic T-cells (CTLs) [ 69 ]. Peptide-specific CD8 + CTLs from normal donors were generated and pulsed with autologous DCs.…”
Section: Reviewmentioning
confidence: 99%